2005
DOI: 10.1088/0143-0807/27/1/016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative measurements of natural convection heat transfer in channels by holographic interferometry and schlieren

Abstract: In this work, natural convection heat transfer in vertical channels is experimentally investigated by applying different optical techniques, namely holographic interferometry and schlieren. Both these techniques are based on the temperature dependence of the air refractive index but they detect different optical quantities and their use involves different instrumentation and optical components. Optical methods, non-intrusive in nature, are particularly suitable for the visualization of flow and thermal fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…HI can be used to obtain wavefront distortion superposed on a holographic plate between two different object waves, one with and one without heat transfer. In this case, less precise optical components are allowed …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HI can be used to obtain wavefront distortion superposed on a holographic plate between two different object waves, one with and one without heat transfer. In this case, less precise optical components are allowed …”
Section: Introductionmentioning
confidence: 99%
“…In many optical methods, the temperature of a fluid is measured from the phase difference in the light rays due to the change in the refractive index. Methods, such as Mach-Zehnder interferometry (MZI), 14,15 lateral shearing interferometry (LSI), 16,17 and holographic interferometry (HI), [18][19][20] have been applied. Owing to the highly accurate, nonintrusive, and full-field measurement, optical methods are preferred for flow visualization and heat transfer analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that the stepped surface helped improve the heat transfer until 23.2% corresponds to an optimum step pitch-to-height ratio equal to 16, while all of the ribbed surfaces decrease the heat transfer performance. Tanda [21,22]; Ambrosini and Tanda [23] analyzed experimentally the natural convection inside a vertical channel formed with a ribbed wall and an opposing adiabatic smooth wall. The natural convection from a grooved plate with different sizes of the grooves has been studied experimentally and numerically by Kwak and Song [24].…”
Section: Introductionmentioning
confidence: 99%
“…Digital holography has a huge number of practical applications, such as microscopy imaging, 1-6 information encryption 7, 8 object recognition, 9 data storage, 10 terahertz imaging, 11,12 measurements of thermal fields, [13][14][15][16][17] monitoring of a singlet oxygen in solutions, 18 measuring statistics of hydrodynamics facilities, [19][20][21][22] testing vibrations, 23 investigations of strained surfaces, 24,25 and objects displacements. 26 In digital holography, there are specific problems, such as zero-order and conjugate images, sampling, sensitivity to vibration of optical components.…”
Section: Introductionmentioning
confidence: 99%